The last movie star [videorecording (DVD)] - Rifkin, Adam, 1966-; Reynolds, Burt; Chase, Chevy; Winter, Ariel, 1998- (Lionsgate, 2018)
Vic Edwards was the biggest star in Hollywood, a college football legend turned stunt double turned leading man. Now in his eighties, he's convinced by an old friend to accept an invitation to receive a Lifetime Achievement Award at a two-bit film festival in Nashville. The trip launches him on both a hilarious fish-out-of-water adventure and an unexpectedly poignant journey into his past.